THE INFLUENCE OF DIGITAL BANKING SERVICES ON CUSTOMER SATISFACTION AT PT BANK PERMATA BANJARMASIN - Minarti Limantara; M. Riza Firdaus; Akhmad Supriyanto; Yeni Susanty (Journal of Artificial Intelligence and Digital Economy, 2024)
This research aims to determine the effect of digital banking services on customer satisfaction at PT Bank Permata Banjarmasin. The method used in literature review research is traditional literature review. The article source comes from Google Scholar. There is a screening stage in selecting a journal which consists of 3 stages, namely screening 1 selecting paid and unpaid journals, screening 2 reviewing the title and abstract, screening 3 reviewing the background, methods, results and discussion. The research results show that digital banking customers in North India are completely satisfied with the quality of services provided by digital banking. In addition, 'reliability' has the strongest risk factor impact on customer satisfaction, followed by 'tangibility' and 'responsiveness'. Reliability, tangibility, responsiveness and guarantee have a positive influence on customer satisfaction (P-value 0.05). The study also recommends that the regulatory body responsible for administering financial regulations in Malaysia should provide standard guidelines and encourage all banks in the country to properly implement digital service quality improvements. Banks should invest in DBC and develop it because DBC is a key determinant in increasing customer satisfaction through higher levels of adoption/diversification, improved service quality, and greater benefits